2014
DOI: 10.1080/13607863.2014.954525
|View full text |Cite
|
Sign up to set email alerts
|

The lifelong struggle of Finnish World War II veterans

Abstract: The war overshadowed the whole lifespan of the veterans, but in old age they finally felt free. Since war experiences vary depending on historical context, a formal theory would require additional research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Since this study had only 8 participants, analysis in distinguishable features among the reported experiences was limited. Lastly, because the focus of this research was not in quantifying the intensity of the adverse event or PTG but the exploration of the personal experience itself, our study did not use quantitative measurement tools (Nguyen et al, 2014 ; Nivala & Sarvimäki, 2015 ). Although exploring unique experiences by utilizing a qualitative research method served as an advantage, we did not use quantitative measurements using a validated scale to objectify their experience.…”
Section: Discussionmentioning
confidence: 99%
“…Since this study had only 8 participants, analysis in distinguishable features among the reported experiences was limited. Lastly, because the focus of this research was not in quantifying the intensity of the adverse event or PTG but the exploration of the personal experience itself, our study did not use quantitative measurement tools (Nguyen et al, 2014 ; Nivala & Sarvimäki, 2015 ). Although exploring unique experiences by utilizing a qualitative research method served as an advantage, we did not use quantitative measurements using a validated scale to objectify their experience.…”
Section: Discussionmentioning
confidence: 99%